Semiotic analysis of Sabah product: durian chocolate - Putera Faidz Hassanal Nordin; Mohamad Puad Bebit (Penerbit UMS, 2021)
This study is research on advertising of locally produced food products, especially in Sabah. It is undeniable that Sabah products are unique and capable of competing at a higher level. However, the impact of local food product labelling on society is still questionable and less encouraging. Proper labelling should make consumers feel safe and secure with the food they choose. The visual aspects of design, colour, and typography were analysed using Semiotic theory to identify the application of graphic elements to the product labelling. The researcher analyses the effectiveness of visual communication in delivering messages and meaning through product labels. Through this research, graphic elements through labelling can be identified, classified by it’s category, and also determining the suitability in the product label. In addition, people's perception of Sabah product can be changed. Mandatory graphic element standards in labels can also be identified and are useful as a guideline.